2005
DOI: 10.1562/2005-01-10-ra-411
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Photobiology of Growth Responses to Two UV‐B Wavebands and UV‐C in Dim‐red‐light‐ and White‐light‐grown Cucumber (Cucumis sativus) Seedlings: Physiological Evidence for Photoreactivation

Abstract: We examined the influence of short-term exposures of different UV wavebands on the elongation and phototropic curvature of hypocotyls of cucumbers (Cucumis sativus L.) grown in white light (WL) and dim red light (DRL). We evaluated (1) whether different wavebands within the ultraviolet B (UV-B) region elicit different responses; (2) the hypocotyl elongation response elicited by ultraviolet C (UV-C); (3) whether irradiation with blue light-enriched white light (B/WL) given simultaneous with UV-B treatments reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…For example, the action spectrum for the inhibition of root elongation in cress resembled the UV absorption spectrum of DNA (Steinmetz and Wellmann 1986). Furthermore, diminished magnitudes of the UVB eVects under accelerated photoreactivation have suggested that DNA damages might be associated with the inhibition of hypocotyl elongation in cucumber (Shinkle et al 2005). On the other hand, for the enhancement eVects of UVB on phytochrome-mediated cotyledon opening, experiments using DNA-repair mutants have indicated that DNA lesions are not involved and, thus, could not constitute the primary event leading to UVB signaling (Boccalandro et al 2001).…”
Section: Involvement Of Unidentiwed Photoreceptor(s) With Maximal Senmentioning
confidence: 99%
“…For example, the action spectrum for the inhibition of root elongation in cress resembled the UV absorption spectrum of DNA (Steinmetz and Wellmann 1986). Furthermore, diminished magnitudes of the UVB eVects under accelerated photoreactivation have suggested that DNA damages might be associated with the inhibition of hypocotyl elongation in cucumber (Shinkle et al 2005). On the other hand, for the enhancement eVects of UVB on phytochrome-mediated cotyledon opening, experiments using DNA-repair mutants have indicated that DNA lesions are not involved and, thus, could not constitute the primary event leading to UVB signaling (Boccalandro et al 2001).…”
Section: Involvement Of Unidentiwed Photoreceptor(s) With Maximal Senmentioning
confidence: 99%
“…Damage may be caused by exposure to relatively high fluence rates of UV-B (Dai et al, 1997;Kim et al, 1998). The effect on the plant will be determined not only by the amount of UV-B but also by the wavelength (Ulm et al, 2004;Shinkle et al, 2004Shinkle et al, , 2005, the degree of prior acclimation, and to some extent by interaction with other environmental factors (Caldwell et al, 2007). High fluence rates of UV-B are known to generate reactive oxygen species (Dai et al, 1997;Allan and Fluhr, 1997;Barta et al, 2004) and to increase levels of signaling molecules involved in wound and defense responses, such as jasmonic acid and ethylene (A-H-Mackerness et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in cucumber (Cucumis sativus) hypocotyls, different UV-B wavebands elicit different growth inhibition and phototropic responses, with the short-wavelength responses most likely mediated by DNA damage signaling (Shinkle et al, 2004(Shinkle et al, , 2005. Similarly, Ulm et al (2004) found that different UV-B wavebands induce distinct gene expression responses in Arabidopsis (Arabidopsis thaliana) and that shorter wavelength UV-B antagonizes the response to longer wavelengths.…”
mentioning
confidence: 99%